Travel risk in the ecotourism industry amid COVID-19 pandemic: ecotourists perceptions - Samdin, Zaiton; Abdullah, Siti Intan Nurdiana Wong; Khaw, Alfred; Subramaniam, Thanam (Taylor Francis, 2022)
The COVID-19 outbreak has caused a global turmoil which restricted movement and consequently, diminishing domestic and international travel. One that is severely affected is ecotourism in National Parks, that involves visiting fragile, pristine and undisturbed natural areas. One of the major concerns for ecotourists in destination decision-making is travel risk that could affect their safety. This study aims to examine their risk perception and how it affects the behaviour of ecotourists in Taman Negara National Park, Malaysia. The data was collected from 406 respondents and analysed using structural equation modelling. It is concluded that risk perception affects tourists’ decision-making, whereby health and safety information preference is the strongest predictor, and media’s influence has a very significant connection. This study has the potential of contributing to the management of ecotourism destinations in times of crisis. It also fills the literature gap on risk perceptions of ecotourists’ during the COVID-19 pandemic.